PENGARUH JUS PEPAYA (Carica papaya) TERHADAP PERUBAHAN WARNA RESIN KOMPOSIT SECARA IN VITRO (PHARMACON, 2016)
PENGARUH  JUS PEPAYA (Carica papaya) TERHADAP PERUBAHAN WARNA RESIN KOMPOSIT SECARA  IN VITRO Deysi R. Genda1), D.H.C Pangemanan1), Michael A. Leman1) 1)Program Studi Kedokteran Gigi Fakultas Kedokteran,Universitas Sam Ratulangi Manado   ABSTRACT Composite resin is a tooth-colored material that is currently interest in community as a restoration material because it has good aesthetic value and can be used for anterior and posterior teeth. Discoloration of composite resin material remain to be a major problem in long-term clinical study. Discoloration of composite resin can be caused by intrinsic and extrinsic factors. One cause of extrinsic composite resin discoloration is  papaya. Purpose of this study is looking for the effect of immersion in juice papaya  solution to discoloration of composite resin. This study is an experimental research laboratory with pre and post test only control design. Sample for this study are thirty of composite resi and  with diameter 5 mm and height 2 mm. This samples divided into 6 groups there are control aquades groups and the treatment group were soaked in the papaya juice with 3 time duration 5,7,and 10 days. After soaking the measured rate of change of colour with spectrophotometer colourflax. These result were statistically tested by one way anova and LSD. One way ANOVA Showed the influence of the path of time soaking papaya juice  solution to discoloration of composite resin (p